2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30870
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Ethical Behavior in Ethical Mentoring Relationships Between Women Graduate Students and Faculty in Science and Engineering

Abstract: in the Department of Engineering Education. Born in Reno, Nevada, she received her bachelor degree in Environmental Engineering from the University of Nevada Reno and her Master's degree in Environmental Engineering from the University of North Dakota. She is currently researching ethical mentoring and hidden curriculum in graduate women students in science and engineering. Her other research interests include mixed-methods research design, integrating sustainability and professional ethics into the engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…All three authors … aim to elevate the voices of women mentors and mentees across science and engineering disciplines, both of which are traditionally male-dominated and technically-and scientifically-demanding." (Gelles et al, 2018) Category 3: Contextualizing methodology…”
Section: Positionality and Engineering Educationmentioning
confidence: 99%
“…All three authors … aim to elevate the voices of women mentors and mentees across science and engineering disciplines, both of which are traditionally male-dominated and technically-and scientifically-demanding." (Gelles et al, 2018) Category 3: Contextualizing methodology…”
Section: Positionality and Engineering Educationmentioning
confidence: 99%
“…A four-factor model was created because of this work, where the relations between hidden curriculum awareness (factor 1), emotions (factor 2), self-efficacy (factor 3), and self-advocacy (factor 4) were explored across ~58 colleges of engineering and 984 engineering faculty and students in the U.S. From the validated instrument (UPHEME; Villanueva et al, 2020), Sellers & Villanueva (2021) analyzed a subset of strategies used by over one hundred and fifty-four BIPOCx individuals in engineering as they coped with the acquired HC. The authors found that advocacies taken by individuals, through self-advocacy (or their willingness to enact advocacy and speak up about a matter to improve their quality of life; Gelles et al, 2019) resulted in three strategies: 1.…”
Section: Hidden Curriculummentioning
confidence: 99%
“…Individuals process and respond to HC by recognizing it (awareness), processing it (emotions), deciding what they can do about it (self-efficacy), and acting (selfadvocacy) [2], [4]- [7], [9], [11], [12]. Previous research characterized individuals' responses to HC into three categories: 1) minimal/no action, 2) negotiating self, and 3) changing the environment [2].…”
Section: Hc In Engineeringmentioning
confidence: 99%